Decreased retinal thickness in preschool offspring of maternal gestational hypertension: the Nanjing Eye Study. Issue 6 (11th February 2020) - Zhao, Xiaoyan; Li, Rui; Huang, Dan; Tong, Haohai; Zhu, Hui; Wang, Yue; Zhang, Xiaohan; Hao, Qingfeng; Sun, Qigang; Liu, Hu
Abstract: Purpose: To evaluate the influence of maternal gestational hypertension (GH) on retinal thickness of 5–6‐year‐old children, including macular thickness, ganglion cell‐inner plexiform layer (GC‐IPL) thickness and peripapillary retinal nerve fibre layer (RNFL) thickness. Methods: As part of Nanjing Eye Study, comprehensive ocular examinations were conducted in children aged 61–72 months, including noncycloplegic refraction, ocular biometric parameters and retinal parameters. Retinal thickness was measured by Spectral Domain‐Optical Coherence Tomography. Data on pregnancy and birth history were obtained from a detailed questionnaire completed by parents. Results: Among 1062 children [mean age (standard deviation): 66.9 (3.4) months] with complete from eye examination and questionnaire, 30 (2.8%) children were born with maternal GH. In generalized linear models (adjusted for sex, age, spherical equivalent, axial length, body mass index, birth weight and premature history), children born with maternal GH had thinner average RNFL thickness (100.5 versus 104.4  μ m, p = 0.035), superior RNFL thickness (123.7 versus 132.0  μ m, p = 0.007), superior GC‐IPL thickness (83.7 versus 86.4  μ m, p = 0.005), superior‐nasal GC‐IPL thickness (86.3 versus 88.4  μ m, p = 0.029) and superior outer macular thickness (278.0 versus 283.0  μ m, p = 0.034) than children born with normal pregnancy. Conclusion: Children exposed to maternal GH tended to have thinner macular, RNFL and GC‐IPL thickness. These findings suggest that maternal GH may affect the development of retina in children thus hinders the development of the offspring's nervous system.